Design of a glazed double-façade by means of coupled CFD and building performance simulation. (September 2017) - Colombo, Elia; Zwahlen, Moritz; Frey, Manuel; Loux, Johann
Abstract: Gruner is involved in the engineering for a new eight-story laboratory building with a double-skin glazed façade to be built in Basel. Through the coupling of a Building Performance Simulation (BPS) and a Computational Fluid Dynamics simulation (3D-CFD) with a specifically developed interface which uses the commercial tools IDA-ICE and Star-CCM+, the behavior of the double-façade was investigated for a warm day cycle and effects on the interiors were evaluated. The temperatures and heat gains on the surfaces and internal glazing were determined, and the temperature load for sensitive components was analyzed. The model is also intended to serve in energy optimization over one year by varying design parameters such as, window absorptivity, or the position and size and location of the ventilation slots.